2008
DOI: 10.2147/ndt.s2017
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment of post-stroke depression

Abstract: Mood depression is a common and serious complication after stroke. According to epidemiological studies, nearly 30% of stroke patients develop depression, either in the early or in the late stages after stroke. Although depression may affect functional recovery and quality of life after stroke, such condition is often ignored. In fact, only a minority of patients is diagnosed and even fewer are treated in the common clinical practice. Moreover, the real benefi ts of antidepressant (AD) therapy in post-stroke d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
163
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(170 citation statements)
references
References 92 publications
1
163
3
3
Order By: Relevance
“…According to epidemiological studies, nearly 30% of stroke patients develop depression, either in the early or in the late stages after stroke. Somatic symptoms like psychomotor retardation, and disturbances in appetite, sleep, and sexual interest, depression are commonly observed problems (6,20). In our study, 10% of the patient's depression status was normal, but the others had different level of depression.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…According to epidemiological studies, nearly 30% of stroke patients develop depression, either in the early or in the late stages after stroke. Somatic symptoms like psychomotor retardation, and disturbances in appetite, sleep, and sexual interest, depression are commonly observed problems (6,20). In our study, 10% of the patient's depression status was normal, but the others had different level of depression.…”
Section: Discussionsupporting
confidence: 42%
“…Post-stroke depression affects disability level, cognitive status and vice versa. The frequency of major depression seems to increase during the first year (4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…This result could be associated with the common occurrence of depression among patients after stroke or those with coronary heart disease (27,28).…”
Section: Tab 2 the Univariate Analysis Of The Infl Uence Of Patientmentioning
confidence: 99%
“…In fact, approximately 30 to 40% of stroke survivors will experience clinically significant depression during the first year after stroke 139 and at some point following a stroke 140,141 . Over half of these patients will develop major or minor depression in the acute care rehabilitation settings 142 .…”
Section: Mdd In the Rehabilitation Settingmentioning
confidence: 99%
“…A recent study showed that ten to 15 sessions of rTMS applied on the left DLPFC at a frequency of 10Hz, and an intensity of 110% MT was associated with significant reduction of depressive symptoms by 30% and a remission rate of 10% as compared to placebo intervention. Mild and few adverse effects such as headache were reported [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] . Another advantage of the use of rTMS is the improvement in executive functions by rTMS 150,151 .…”
Section: Mdd In the Rehabilitation Settingmentioning
confidence: 99%